Determinan Multidimensi Pembangunan Ekonomi: Analisis Simultan Modal Manusia, Sumber Daya Alam, dan Kelembagaan - Enni Sari Siregar; Yulia Pratiwi Siregar; Nurintan Siregar (PPJP ULM, 2026)
This study aims to analyze the influence of education, health, mineral resources, forest resources, and institutional quality on economic development in North Sumatra. The data were analyzed using multiple linear regression to determine the impact of each independent variable on the dependent variable. The findings reveal that education, health, mineral resources, and institutional quality have a significant impact on economic development. In contrast, forest resources do not have a significant influence. This suggests that economic development is more heavily driven by human capital quality and institutional frameworks rather than a reliance on forest resources. Consequently, enhancing the quality of education and health, optimizing mineral resource management, and strengthening institutions are critical factors in accelerating regional economic development.